The chaplain grieves in silence: marginalisation, disenfranchised grief, and chaplaincy - Yih, Caroline (Practical theology, 2021)
The palliative chaplains’ role inevitably places them in continual exposure to acute grief and multiple losses, similarly to other healthcare professionals. This experience of professional-related grief has often been ignored and can be described as disenfranchised grief. However, there are different underlying dimensions within this understanding of disenfranchised grief, as experienced by hospital palliative chaplains, which are distinguishable from the grief experiences of their non-chaplain colleagues in the multidisciplinary team. These disparities are often overlooked by the chaplains themselves as well as by their host institution and their care recipients. These cumulative and recurrent experiences of unacknowledged and unattended grief acutely impact the chaplains’ practice on an ongoing basis.In this paper, I explore and expand on the concept of disenfranchised grief as related specifically to the experience of hospital palliative chaplains. I illustrate that the existing framework for understanding professional disenfranchised grief is insufficient to encapsulate the myriad of influences pertinent to the chaplains’ experience in the hospital setting. I analyse and elucidate on these facets of professional disenfranchised grief pertinent to the idiosyncratic nature of the chaplains’ practice.